Characteristics of plasticized PEMAlPVdF-HFP blend polymer electrolyte films doped with lithium triflate salt in electro chromic device - Sim, L.N.; Majid, S.R.; Arof, Abdul Kariem (2010)
Poly( ethyl methacrylate), PEMA and poly(vinylidenefluoride-co-hexafluoropropylene), PVdF-HFP have been blended in the weight ratio 70:30. The blend has been doped with lithium trifluoromethanesulfonate (LiCF3S03) and plasticized ~th ethylene carbonate (EC) and propylene carbonate (PC). The sample 70 wt.% PEMAlPVdF-HFP - 30 wt.% LiCF3S03 exhibits room temperature ionic conductivity of 2.87 x 10-7 Scm-I. The highest conducting sample in the PC plasticized system is 1.46 x 10-6 Scm-I. The highest conducting EC plasticized system has o conductivity of 1.05 x 10-4 Scm-I and designated as 6EC. The plasticized electrolytes are 123 transparent and mechanically stable at room temperature. An electrochromic device (ECD) with configuration glassIFTOIW03/sample/Ce02- Ti02IFTO/glass utilizing S30, 6PC and 6EC as electrolytes have been fabricated. The cyclic voltammogram (CV) of glassIFTOIW03/6ECICe02-Ti02IFTO/glass shows a cathodic peak occurring at -1.3 V upon coloration while an anodic peak is observed at -0.8 V during bleaching process.